Психоэмоциональное состояние беременных с невынашиванием в анамнезе на этапе санаторной реабилитации - Сюсюка, В. Г.; Suzuka, V. G.; Сюсюка, Володимир Григорович («МЕДИ Экспо», 2016)
There was carried out a clinical and psychological examination of 70 women in II and III trimester, whose course of pregnancy was complicated with recurrent miscarriage. Taking into account high percentage of women with trait anxiety in research group that is stable individual feature reflecting susceptibility of person towards anxiety, this fact should be considered as risk factor of recurrent miscarriage.
Psychoemotional state of pregnant women with miscarriage in past medical history at the stage of sanatorium health improvement